2020
DOI: 10.1103/physrevresearch.2.033265
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of pristine and Ni-substituted LaFeO3 from near edge x-ray absorption fine structure experiments and first-principles simulations

Abstract: We present a joint theoretical and experimental study of the oxygen K-edge spectra for LaFeO 3 and homovalent Ni-substituted LaFeO 3 (LaFe 0.75 Ni 0.25 O 3), using first-principles simulations based on density-functional theory with extended Hubbard functionals and x-ray absorption near edge structure (XANES) measurements. Ground-state and excited-state XANES calculations employ Hubbard onsite U and intersite V parameters determined from first principles and the Lanczos recursive method to obtain absorption cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 96 publications
(181 reference statements)
0
28
0
Order By: Relevance
“…DFT+U is only marginally more expensive than DFT within LDA or GGA, while significantly improving various properties of materials such as transition-metal compounds. An extension of DFT+U to take into account inter-site Hubbard V interactions (DFT+U+V [35]) was introduced, showing success in describing materials with strong inter-site electronic hybridizations (i.e., covalent interactions) [35][36][37][38][39][40][41]. Finally, there are various methods beyond DFT, including many-body perturbation theory (MBPT) [42] (e.g., GW approximation [43][44][45][46]) and dynamical mean field theory (DMFT) [47][48][49][50][51], which are widely used for predicting optical properties of (strongly) correlated systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT+U is only marginally more expensive than DFT within LDA or GGA, while significantly improving various properties of materials such as transition-metal compounds. An extension of DFT+U to take into account inter-site Hubbard V interactions (DFT+U+V [35]) was introduced, showing success in describing materials with strong inter-site electronic hybridizations (i.e., covalent interactions) [35][36][37][38][39][40][41]. Finally, there are various methods beyond DFT, including many-body perturbation theory (MBPT) [42] (e.g., GW approximation [43][44][45][46]) and dynamical mean field theory (DMFT) [47][48][49][50][51], which are widely used for predicting optical properties of (strongly) correlated systems.…”
Section: Introductionmentioning
confidence: 99%
“…In all these ab initio methods for computing U, key is the choice of the Hubbard projector functions. There are different types of Hubbard projectors [80], including nonorthogonalized atomic orbitals [34,[81][82][83], orthogonalized atomic orbitals [36,37,39,84], nonorthogonalized Wannier functions [85], orthogonalized Wannier functions [86], linearized augmented plane-wave approaches [87], and projector-augmented-wave projector functions [88,89]. It is well known that the values of the computed Hubbard U parameters strongly depend on the type of Hubbard projectors used [79,84].…”
Section: Introductionmentioning
confidence: 99%
“…Also, we are not aware of any XANES measurements for β-MnO 2 , hence we cannot verify the accuracy of empty-states PDOS computed in this work. However, we want to point out that in the previous study of the XANES spectra of pristine and Ni-substituted LaFeO 3 we found that DFT+U and DFT+U +V with OAO projectors give results that are in fair agreement with the experimental XANES spectra [92]. Therefore, high-resolution XPS and XANES experiments on β-MnO 2 are called for.…”
Section: F Projected Density Of Statesmentioning
confidence: 87%
“…[61]). In particular, we highlight here nonorthogonalized atomic orbitals (NAO) [56,62], orthogonalized atomic orbitals (OAO) [31,32,63], nonorthogonalized Wannier functions (NWF) [64], orthogonalized Wannier functions (OWF) [65], linearized augmented plane-wave (LAPW) approaches [66], and projector-augmented-wave (PAW) projector functions [67,68]. A common feature of all these projector functions is that they are spatially localized and depend explicitly on atomic positions; hence, an extra term appears when computing derivatives of the Hubbard corrective energy with respect to atomic displacements (Pulay force) or strain (Pulay stress).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present a derivation that allows us to calculate Pulay (Hubbard) forces for the case of OAO projector functions, by starting from the expressions for the Hubbard force in the case of NAO [69,70] and using the Hubbard parameters U and V computed using density-functional perturbation theory (DFPT) [57,63]. We present a detailed mathematical formulation of the derivative of the inverse square root of the orbital overlap matrix as a closed-form solution of the Lyapunov (Sylvester) equation, which is the main result of the present the formalism, and we compare it with other techniques that were used in literature to compute such a derivative.…”
Section: Introductionmentioning
confidence: 99%